COMBINING ABILITY AND GENE ACTION FOR QUALITY CHARACTERS IN RICE (Oryza sativa L.) - CHINNATHAMBI PON RENUKA DEVI, S. SUGANTHI, A. KAMARAJ R. ANANDAN; P. SATHEESH KUMAR* (The Journal of Research ANGRAU, 2019)
A line X tester analysis was studied in rice with seven lines and four tester parents to identify suitable general and specific combiner for breeding programme. The variances due to SCA were of greater magnitude than GCA for all the traits indicating the preponderance of non-additive gene action for these characters. Among the lines STBN 25, STBN 26 and RNR 15048 and testers ADT 43 and IR 64 were considered as the best general combiners for grain yield per plant, while hybrids RNR 15048/ADT 43, MTU 1010 / IR 64, STBN 25 / IR 64, STBN 14 / ADT 37 and STBN 26 / ADT 43 as good specific combiners for grain yield per plant. The crosses RNR 15048 / ADT 43 and MTU 1010 / IR 64 exhibited good SCA effects for grain yield per plant and quality traits, so these hybrids may be exploited for better yield and quality either by exploiting them through heterosis breeding or multiple cross-breeding programme for obtaining transgressive segregants and broad genetic base population for improvement in quality rice.